Perioperative intravenous lidocaine for postoperative pain in patients undergoing breast surgery: a meta-analysis with trial sequential analysis of randomized controlled trials - Li, Jia; Huang, Jiao; Yang, Jiang-tao; Liu, Jing-chen (Frontiers in Oncology, 2023)
Background The effectiveness of intravenous lidocaine infusion in managing acute and chronic pain following breast surgery has been a topic of debate. This meta-analysis aims to assess the impact of perioperative intravenous lidocaine on the relief of postoperative pain among patients undergoing breast surgery. Methods A systematic search of databases was conducted to identify randomized controlled trials (RCTs) that compared the effects of intravenous lidocaine infusion with placebo or routine care in patients undergoing breast surgery. The primary outcome of interest was the occurrence of chronic post-surgical pain (CPSP) at the longest follow-up. Meta-analyses, incorporating trial sequential analysis, were performed using a random-effects model to assess the overall effect. Results A total of twelve trials, involving 879 patients, were included in the analysis. Perioperative intravenous lidocaine demonstrated a significant reduction in the incidence of CPSP at the longest follow-up (risk ratio [RR] 0.62, 95% confidence interval [CI] 0.48-0.81; P = 0.0005; I2 = 6%). Trial sequential analysis (TSA) indicated that the cumulative z curve crossed the trial sequential monitoring boundary for benefit, providing sufficient and conclusive evidence. Furthermore, intravenous lidocaine was associated with decreased opioid consumption and a shorter length of hospital stay. Conclusion Perioperative intravenous lidocaine is effective in relieving acute and CPSP in patients undergoing breast surgery. Systematic review registration https://inplasy.com/, identifier INPLASY2022100033.